MOTIVATIONAL STRATEGIES IN TEACHING SPEAKING SKILL - Sa’diyah, Arofiatus (Journal of English Teaching, Literature, and Applied Linguistics, 2021)
Motivation plays an important role in learning process, but it is generally known as the main problem in English as foreign language learning process. Most of the researches and studies pay high attention to this problem as it seems to be the trickiest challenges faced by teachers. Moreover in teaching speaking, the teacher should have high sensitivity to identify whether the students really have low motivation in oral production or it is caused by other factors, because low of motivation makes the students unable to achieve the goal of language learning. This paper discusses the motivational strategies in teaching speaking skill to the students who has low motivation also provide recommendation for English teacher to have successful implementation regarding to solve student’ low motivation in speaking skill.